2006
DOI: 10.1536/ihj.47.107
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Expression of Cardiac Adiponectin in Leptin-Deficient Mice With Viral Myocarditis

Abstract: SUMMARYA mouse model of encephalomyocarditis (EMC) virus-induced myocarditis was used to investigate the expression of adiponectin in damaged cardiomyocytes. We intraperitoneally injected EMC virus into leptin-deficient ob/ob (OB) mice and wild-type (WT) mice. OB mice were divided into two subgroups consisting of mice with no intervention and mice receiving leptin replacement starting simultaneously with viral inoculation. We determined differences in heart weight, cardiac histological score, numbers of infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…13) In agreement with this previous study, we found that adiponectin mRNA expression levels were markedly higher in WY14643-treated mice on days 0, 4, and 9, and that the myocardial diameter decreased and the inflammation improved. These findings imply that the adiponectin-associated antihypertrophic and anti-inflammatory effects might be involved in WY14643 treatment of EMCv-inoculated KKAy mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…13) In agreement with this previous study, we found that adiponectin mRNA expression levels were markedly higher in WY14643-treated mice on days 0, 4, and 9, and that the myocardial diameter decreased and the inflammation improved. These findings imply that the adiponectin-associated antihypertrophic and anti-inflammatory effects might be involved in WY14643 treatment of EMCv-inoculated KKAy mice.…”
Section: Discussionsupporting
confidence: 92%
“…Some slices were stained with hematoxylin-eosin to assess the severity of myocardial necrosis and inflammatory cell infiltration according to previously described scales. 13,14) The LV wall thickness (LW) and LV cavity (LC) dimensions were measured with the slice at the maximal circumference of the ventricle, as described by Matsumori, et al 15) (Figure 1). The diameter of the myocardial fiber in the lateral LV wall was determined as described previously.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…34) In addition, Takahashi, et al found that impaired expression of cardiac adiponectin may contribute to the progression of viral myocarditis through enhanced expression of TNF-α in leptin-deficient mice. 35) They speculated that local expression of adiponectin in the damaged heart may be a compensatory phenomenon against severe inflammatory conditions such as viral myocarditis. 35) These anti-inflammatory effects of adiponectin may contribute to its protective features against the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…35) They speculated that local expression of adiponectin in the damaged heart may be a compensatory phenomenon against severe inflammatory conditions such as viral myocarditis. 35) These anti-inflammatory effects of adiponectin may contribute to its protective features against the development of atherosclerosis. Conclusions: In conclusion, our findings indicate an inverse relation exists between serum concentrations of adiponectin and subclinical carotid atherosclerosis in patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 99%